The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/(sici)1096-9861(19961111)375:2<274::aid-cne7>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mRNAs encoding the limbic system‐associated membrane protein (LAMP): I. Adult rat brain

Abstract: The search for molecular markers common to neural structures that are functionally related has become an attractive strategy for neurobiologists interested in identifying mechanisms involved in the formation of patterned connections. One such molecule is the limbic system-associated membrane protein (LAMP), a 64-68 kDa glycoprotein that is expressed in the soma and dendrites of subpopulations of adult neurons in the brain that are functionally associated with classic limbic structures. Such patterned molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 75 publications
(85 reference statements)
1
19
0
Order By: Relevance
“…At least three families of growth-regulating molecules have been identified as candidates for the guidance signals in the developing cortex and thalamus. First, the Ig superfamily members such as the limbic-associated membrane protein (LAMP) and neurotrimmin are found in distinct limbic and primary sensory and motor regions, respectively (19,36,37), and have been shown to promote neurite outgrowth in a homophilic fashion in vitro (19,38), indicating that positive guidance cues are essential for appropriate targeting of axon populations in the cortex. This notion is supported by in vivo transplant studies in which LAMP expression correlates precisely with the ability to form limbic thalamocortical (34) and cortico-cortical (39) connections of each graft with the host brain.…”
Section: Discussionmentioning
confidence: 99%
“…At least three families of growth-regulating molecules have been identified as candidates for the guidance signals in the developing cortex and thalamus. First, the Ig superfamily members such as the limbic-associated membrane protein (LAMP) and neurotrimmin are found in distinct limbic and primary sensory and motor regions, respectively (19,36,37), and have been shown to promote neurite outgrowth in a homophilic fashion in vitro (19,38), indicating that positive guidance cues are essential for appropriate targeting of axon populations in the cortex. This notion is supported by in vivo transplant studies in which LAMP expression correlates precisely with the ability to form limbic thalamocortical (34) and cortico-cortical (39) connections of each graft with the host brain.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, Kilon immunoreactivity was detected on the dendrites and somata of pyramidal neurons in the hippocampus CA1 region and in the cerebral cortex, an expression pattern believed to be similar to that of LAMP Levitt, 1989, Pimenta et al, 1996;Reinoso et al, 1996). We used in situ hybridization to analyze the distribution of Kilon in the developing and adult rat brain in comparison to LAMP and found that Kilon mRNA expression shows clear differences from that of LAMP during development, leading to a pattern in the adult hippocampus in which Kilon mRNA synthesis is restricted almost exclusively to the adult DG.…”
mentioning
confidence: 85%
“…U31554) were used. As an additional control for the specificity of the LAMP signal, we used the antisense oligonucleotide designed by Reinoso et al (1996) (5Ј-GTG GTA CGG CCA GAC TGA TGG ATC CGT TGA TTC CTC TCA CCG ACC CGG GTC TG-3Ј) complementary to bases 973-1025 of the rat LAMP cDNA (GenBank accession no. U31554).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…The limbic system-associated membrane protein (LAMP), a cell adhesion molecule (CAM) of the IgLON family expressed in cortical and subcortical limbic-associated regions of the developing and adult brain [5,6,20,29,39,44,54] is one such molecule. The protein exhibits 99% homology between rodent and human [38] and there is a close correlation between Lsamp mRNA and protein distribution patterns in rat [29,39,44,54], monkey [5,6], and human [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The protein exhibits 99% homology between rodent and human [38] and there is a close correlation between Lsamp mRNA and protein distribution patterns in rat [29,39,44,54], monkey [5,6], and human [42,43]. Experimental manipulations of LAMP in vitro result in altered axon targeting and neurite growth [13,24,31,41,56].…”
Section: Introductionmentioning
confidence: 99%